1987
DOI: 10.1093/schbul/13.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Process-reactive Dimension and Outcome for Narrow Concepts of Schizophrenia

Abstract: The data presented by the authors suggest a more successful prediction of outcome by the process-reactive dimension when it is applied to schizophrenic patients defined according to broad concepts of schizophrenia (e.g., DSM-II) than to narrow concepts of schizophrenia (e.g., DSM-III). Research indicates that the DSM-III is more likely than the DSM-II diagnosis to be composed of "poor prognosis" schizophrenia, as defined by the classical prognostic indicators. In general, the overall results could support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Haas et al), which confers a better outcome than schizophrenia or schizoaffective disorder. Thus, our findings support suggestions (4,5) that the inclusion of a 6-month duration of illness criterion for DSM-III-R and, subsequently, DSM-IV diagnoses would eliminate much if not all of the predictive effect seen in earlier studies of onset of psychosis. Although three studies (12, 21; unpublished 1994 paper by G.L.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Haas et al), which confers a better outcome than schizophrenia or schizoaffective disorder. Thus, our findings support suggestions (4,5) that the inclusion of a 6-month duration of illness criterion for DSM-III-R and, subsequently, DSM-IV diagnoses would eliminate much if not all of the predictive effect seen in earlier studies of onset of psychosis. Although three studies (12, 21; unpublished 1994 paper by G.L.…”
Section: Discussionsupporting
confidence: 82%
“…That study, which used ICD-9 and the computer algorithm CATEGO to define the diagnostic categories, found onset type to be one of the two most important predictors of 2-year outcome (the other was settingi.e., developed versus developing country). However, in the mid-1980s, retrospective studies found that the 6-month duration of illness criterion required for the DSM-III diagnosis of schizophrenia reduced the number of patients considered to have an acute onset, making it more difficult to predict outcome in young patients with recent-onset schizophrenia (4,5).…”
mentioning
confidence: 99%
“…Marital status did not predict readmission risk at any discharge in this study. Other studies have also failed to show any association between marital status and outcome when adjusting for age at onset and gender (Rosen et al 1971;Munk-Jergensen et al 1991) and it seems plausible that marital status is too weak an indicator of both prior social adjustment (Har-row et al 1986;Harrow & Westermeyer, 1987) and current family environment to provide any further prediction of readmission risk, once age at onset and other relevant predictors have been taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found that the broader DSM II criteria resulted in a better prognosis than then more stringent DSM III diagnostic criteria [21], meaning that DSM III definition captures a more chronic form of SZ. Patients diagnosed with SZ using DSM III were more homogenous and had a worse prognosis overall [22]. gender) had a higher predictive value, because a number of the female patients with better prognosis did not meet the stricter DSM III criteria for inclusion in the study.…”
Section: Post-antipsychotic Era Institutionaliza-tion Studiesmentioning
confidence: 99%